Development of Interactive Learning Media Canva Based on Virus Material at High School - Delsa Mahmudah; Marlinda Nilan Sari Rangkuti (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Virus material in biology subjects is abstract and often difficult for students to understand, which results in low effectiveness of the learning process in the classroom. This study aims to develop Canva-based interactive learning media on virus material, as well as to test its feasibility, practicality, and effectiveness in improving student learning outcomes. This research is development research (R&D) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects included material experts, media experts, learning experts, biology teachers, and grade X students at High School 1 Labuhan Deli. Data was collected through interviews, questionnaires, and learning outcome tests (pretest and posttest), which were then analyzed descriptively, qualitatively, and quantitatively. The research findings indicated that this Canva-based learning media is categorized as "Very Feasible" with validation scores of 93.33% from material experts, 98.33% from media experts, and 86.11% from learning experts. The media’s practicality was rated "Very Good" with a 93.33% response from biology teachers, as well as 91.94% in small groups and 90.45% in large group trials. In terms of effectiveness, there was a significant increase in student learning outcomes with an average score from 65.21 to 92.79. An N-Gain score of 0.79 (79.45%) indicates high effectiveness. This research contributes to the development of practical and effective digital learning media for biology teachers in visualizing abstract material, thereby supporting the optimization of the teaching and learning process at the high school level.